The “weak-veined” Lasioglossum in Australia, New Zealand and West New Guinea, with descriptions of three new subgenera (Hymenoptera: Apoidea: Halictidae) - Walker, Kenneth L. (Zootaxa, 2025)
Currently, all Australian and New Zealand “weak-veined” Lasioglossum Curtis 1883 species are placed in the subgenus Austrevylaeus Michener 1965 which has L. sordidum (Smith 1853), a New Zealand species, as the type species. A comparative analysis was conducted for Austrevylaeus against three Northern Hemisphere “weak-veined” subgenera Evylaeus Robertson 1902b, Hemihalictus Cockerell 1897 and Sphecodogastra Ashmead 1899. This resulted in a reclassification of the Australian “weak-veined” Lasioglossum fauna with three new subgenera erected: Cnephalictus new subgenus, Enigmalictus new subgenus and Evyloides new subgenus and Austrevylaeus is now restricted to the New Zealand species. Diagnoses are provided for the Australian and New Zealand “weak-veined” subgenera. All Australian species are described, in some cases with one sex for the first time. In addition, citation lists, type designations, type depositories, synonymy lists, diagnoses, distribution maps, SEMs of female inner metatibial spurs, montage images (specimen and male genitalia), examined material, etymologies of species names and comments on taxonomy and floral visitations are presented. Keys to both sexes for Australian and New Zealand species are provided. The New Zealand “weak-veined” Lasioglossum fauna contains three species: subgenus Austrevylaeus—L. mataroa Donovan 2007, L. maunga Donovan 2007 and L. sordidum. The Australian “weak-veined” Lasioglossum fauna contains 11 species. Valid, new taxa and new synonyms include: subgenus Cnephalictus—L. amber new species, L. bernhardti new species, L. contaminatum (Cockerell 1910a) and L. lorienae new species; subgenus Enigmalictus—L. blighi (Cockerell 1915) (junior subjective synonym is Halictus pertasmaniae Rayment 1953 new synonymy), L. disclusum (Cockerell 1914) (junior subjective synonym is H. pertribuarius Rayment 1935 new synonymy), L. excelsum new species, L. exoneuroides (Rayment 1953) (junior subjective synonym is H. portlandensis Rayment 1953 new synonymy), L. melanurus (Cockerell 1919) and L. rufibasis (Cockerell 1923); subgenus Evyloides—L. ewarti (Cockerell 1910a). A re-evaluation of the number of subgenera and species included in the world-wide Lasioglossum “strong-veined” and “weak-veined” series is presented. Examination of specimens in the Bishop Museum revealed the first known specimen and new species of a “weak-veined” Lasioglossum from West Papua (Indonesia) with an elongated head length—L. oblongulum new species. The head elongation and subgeneric placement of this species are discussed.